Quantum scale anomaly and spatial coherence in a 2D Fermi superfluid - Murthy, Puneet A.; Defenu, Nicolò; Bayha, Luca; Holten, Marvin; Preiss, Philipp; Enss, Tilman; Jochim, Selim (Science, 2019)
A quantum breakdown - At low temperatures, two-dimensional (2D) systems with contact interactions are expected to exhibit quantum anomalies—a breakdown of scaling laws that characterize such systems in the classical regime. Signatures of these anomalies have been observed in the real-space properties of 2D Fermi gases, but the effect is much less pronounced than expected on theoretical grounds. Murthy et al. studied the momentum-space profiles of 2D superfluids of fermionic atoms. They initially perturbed the gas and then monitored the momentum distribution of its atoms. In the regime of strong interactions between the atoms, the momentum profiles deviated markedly from the classical scaling. - Science, this issue p. 268 - Quantum anomalies are violations of classical scaling symmetries caused by divergences that appear in the quantization of certain classical theories. Although they play a prominent role in the quantum field theoretical description of many-body systems, their influence on experimental observables is difficult to discern. In this study, we discovered a distinctive manifestation of a quantum anomaly in the momentum-space dynamics of a two-dimensional (2D) Fermi superfluid of ultracold atoms. The measured pair momentum distributions of the superfluid during a breathing mode cycle exhibit a scaling violation in the strongly interacting regime. We found that the power-law exponents that characterize long-range phase correlations in the system are modified by the quantum anomaly, emphasizing the influence of this effect on the critical properties of 2D superfluids. - Momentum-space profiles reveal the breakdown of classical scaling in the strongly interacting regime. - Momentum-space profiles reveal the breakdown of classical scaling in the strongly interacting regime.